2019
DOI: 10.1159/000495666
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Center Retrospective Study of Patients with Double Primary Cancers: Breast Cancer and <b><i>EGFR</i></b>-Mutant Non-Small Cell Lung Cancer

Abstract: Background: Second primary malignancies (SPM) in the lung are not common in breast cancer (BC) patients. EGFR-mutant lung cancer (LC) is a separate molecular subset, and the co-existence of EGFR-mutant LC and BC has not been explored. We hypothesized that EGFR-mutant LC patients could have higher rates of primary BC than those with EGFR-wild type (WT). Methods: We collected data on clinical and molecular characteristics and outcomes of female patients with LC and a previous or simultaneous history of primary B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…Previous study showed that the EGFR mutation was significantly increased in female patients with LC, and the expression [13]. In a single-center retrospective study, it was found that the incidence of primary BC in patients with EGFR mutated NSCLC may be higher than patients without EGFR mutation [14]. These studies suggest that ER may represent a common factor in the occurrence and development of BC and LC, but in this study, we failed to associate BC-LC with ER status.…”
Section: Discussionmentioning
confidence: 96%
“…Previous study showed that the EGFR mutation was significantly increased in female patients with LC, and the expression [13]. In a single-center retrospective study, it was found that the incidence of primary BC in patients with EGFR mutated NSCLC may be higher than patients without EGFR mutation [14]. These studies suggest that ER may represent a common factor in the occurrence and development of BC and LC, but in this study, we failed to associate BC-LC with ER status.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a study reported that the risk of developing an SPLC after invasive breast cancer varied with estrogen receptor status ( 10 ). Another single-center, retrospective study indicated that a higher proportion of patients with EGFR-mutant lung cancer had previous breast cancer compared to patients with EGFR non-mutant lung cancer ( 11 ). However, the association between HER2 overexpression and EGFR mutations was not analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that the incidence of SPLC was higher in human epidermal receptor 2 (HER2) negative breast cancer survivors than in HER2 positive breast cancer survivors. A recent retrospective study showed that the frequency of previous breast cancer was higher in patients with epidermal growth factor receptor (EGFR)-mutant lung cancer than in those with EGFR wild-type lung cancer ( 11 ). The family of EGFR receptors plays an important role in cell proliferation ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps, this is related to elevated hormone levels, which may drive the development of both cancers simultaneously although this may also be confounded by closer follow-up and use of radiologic imaging immediately following BC diagnosis. 21,23,35 In two recent SEER database studies, LC incidence was numerically higher after triple-negative BC (TNBC), although for one of the studies, this difference was not statistically significant 6,21 (Table 3). Compared to patients with hormone-positive (HR+) BCLC, those with HR− or TNBC also correlated with a poorer prognosis.…”
Section: Er/pr/her2 Receptorsmentioning
confidence: 98%
“…In a retrospective study looking at 356 LC patients with EGFR data available, 17.7% (11/62) with EGFR mutations had BC compared to 1.02% (3/294) of EGFR wild-type patients. 23 Another study investigated the relationship between EGFR mutational status and hormone receptor expression in patients with simultaneous LC and BC. Unlike the phase II trial involving fulvestrant plus erlotinib, patients with EGFR-mutated LC in this study were shown to correlate with HR+ LC tissue (34.4% had HR+ compared to 0% for EGFR wild-type LC).…”
Section: Risk Factorsmentioning
confidence: 99%